Meningkatkan Fungsi Pengawasan Pemimpin Terhadap Kinerja Pegawai Di Badan Amil Zakat Nasional Kabupaten Ogan Komering Ulu - Cllara Shintya Lugita; Candra Darmawan (Social Science and Contemporary Issues Journal, 2023)
This research is entitled "Improving the Supervisory Function of Leaders on Employee Performance at the National Zakat Amil Agency (BAZNAS) OKU Regency". The aim of this research is to find out how to improve the supervisory function of leaders on employee performance at the National Zakat Amil Agency (BAZNAS) OKU Regency. This type of research is field research, namely research that collects data in the field, located at BAZNAS, OKU District. Data collection techniques in this research are observation, interviews and documentation. This data analysis technique is qualitative descriptive through three stages, namely data reduction, data presentation, and drawing conclusions. This research uses supervision theory by Kartono and employee performance theory by Robbins. Supervision at BAZNAS OKU District uses a collegial collective system, which means that supervision is carried out by 4 people, namely the Chairman, Deputy Head I, Deputy Head II and Deputy Deputy III. To improve the supervisory function of employee performance in this research, as implemented by BAZNAS, OKU District places more emphasis on supervision indicators: Determining Implementation Measures, Providing Assessments, and Carrying out Corrections. The supervision process at BAZNAS OKU Regency uses direct supervision through direct inspections, on-site observations and on-site reports. The types of supervision used are the type of preliminary supervision (feed forward control), the type of supervision carried out simultaneously with the implementation of activities (current control) and the type of feedback supervision (feedback control). The implementation of the supervisory process carried out by the leadership on employee performance at BAZNAS OKU District has not been carried out optimally. Because daily meetings are rarely implemented, which are usually held after employees have finished their work. However, this is still effective for employees, therefore employees can produce good performance so that the institution's goals can be realized optimally.